Analisis Pengaruh Implementasi POJK No. 11/POJK.03/2020 Sebagai Kebijakan Countercyclical Dampak Penyebaran Covid-2019 Terhadap ROA dan NPF Pada Bank Pembiayaan Rakyat Syariah - Fauzi Fauzi; Rita Irviani; Rustam Efendi; Muhammad Wardani Anwar (ITB AAS INDONESIA Surakarta, 2023)
The impact of the COVID-19 pandemic on declining people's income and Indonesia's economic growth has made the Financial Services Authority (OJK) issue POJK No. 11/POJK.03/2020 concerning National Economic Stimulus as a countercyclical policy on the Impact of the Spread of Coronavirus Disease 2019 as an anticipatory effort in dealing with the COVID-19 pandemic, as well as encouraging the optimization of banking operational activities amid the COVID-19 pandemic. This study aims to determine the effect of the implementation of POJK No. 11/POJK.03/2020 as a countercyclical policy on the impact of the spread of coronavirus disease 2019 on Return on Assets (ROA) and Non Performing Financing (NPF) on BPRS Mitra Agro Usaha. This type of research is quantitative research. The data sources in this study are primary data and secondary data. The research data was taken from January 2019-March 2021. The data analysis technique uses a normality test, homogeneity test, dummy variable simple regression test, partial test (t test), correlation coefficient (r), coefficient of determination (r2), and independent sample t-test. The results of this study state that POJK No. 11/POJK.03/2020 as a countercyclical policy on the impact of the spread of coronavirus disease 2019 does not have a significant effect on Return on Assets (ROA) on BPRS Mitra Agro Usaha and POJK No. 11/POJK.03/2020 as a countercyclical policy impacting the spread of coronavirus disease 2019 has a positive effect and significant on Non Performing Financing (NPF) on BPRS Mitra Agro Usaha.